Exploiting EPR to elucidate fine and hyperfine interactions in complex chemical and biological systems - Moise, G (2020)
The research presented in this thesis is concerned with the applications of Electron Paramagnetic Resonance (EPR) spectroscopy to the study of porphyrin systems and cryptochrome proteins. In particular, the fine and hyperfine interactions measured using EPR are exploited to further our understanding of both the intricate electronic and spatial structure of these systems as well as their potential future applications.